2021
DOI: 10.1177/07482337211034711
|View full text |Cite
|
Sign up to set email alerts
|

Nickel nanoparticles induce hepatotoxicity via oxidative and nitrative stress-mediated apoptosis and inflammation

Abstract: Nickel nanoparticles (Ni NPs) are utilized extensively in various industrial applications. However, there are increasing concerns about potential exposure to Ni NPs and consequent health effects. The aim of this study was to assess Ni NPs-induced liver toxicity in Sprague Dawley rats. Twenty-five rats were exposed to Ni NPs via intraperitoneal injection at doses of 15, 30, and 45 mg/kg per body weight for 28 days. Results from ICP-MS analysis showed an increase in the concentration of Ni NPs in a dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…This is associated with a depletion of the hepatic glutathione levels [23] and nickel accumulation in the liver [196]. Finally, liver injury by nickel nanoparticles can also be triggered by nitrative stress, causing apoptosis and inflammation [197]. Evidence for the nitrative stress was provided by increased specific stress markers like iNOS (inducible nitric oxide synthase) or NO (nitric oxide) [197].…”
Section: Nickelmentioning
confidence: 99%
See 1 more Smart Citation
“…This is associated with a depletion of the hepatic glutathione levels [23] and nickel accumulation in the liver [196]. Finally, liver injury by nickel nanoparticles can also be triggered by nitrative stress, causing apoptosis and inflammation [197]. Evidence for the nitrative stress was provided by increased specific stress markers like iNOS (inducible nitric oxide synthase) or NO (nitric oxide) [197].…”
Section: Nickelmentioning
confidence: 99%
“…Finally, liver injury by nickel nanoparticles can also be triggered by nitrative stress, causing apoptosis and inflammation [197]. Evidence for the nitrative stress was provided by increased specific stress markers like iNOS (inducible nitric oxide synthase) or NO (nitric oxide) [197]. Studies with the zebrafish model failed to provide additional conceptual views on initiation or perpetuation the nickel injury [198].…”
Section: Nickelmentioning
confidence: 99%
“…17,18 The hepatotoxicology mechanism of Ni mainly focus on the oxidative stress, DNA damage, apoptosis, and inflammation. 17,[19][20][21][22] Also, our previous studies have showed that dietary NiCl 2 in excess of 300 mg/kg can cause apoptosis, cell cycle arrest and inflammatory in the liver of broilers. 17 And, NiCl 2 treatment could induce hepatocellular ferroptosis.…”
Section: Introductionmentioning
confidence: 99%
“…This was associated with both, depletion of the hepatic glutathione levels [ 12 ] and Ni accumulation in the liver [ 82 ]. Liver injury by Ni nanoparticles was also triggered by nitrative stress, causing apoptosis and inflammation [ 83 ]. Evidence for the nitrative stress concept was provided by augmented specific stress markers like iNOS (inducible nitric oxide synthase) or NO (nitric oxide).…”
Section: Nickelmentioning
confidence: 99%